Glycosylation Gap in type II diabetes mellitus patients with vitamin D deficiency - Alkataan, Muhammad A. Ahmed; Ibrahim, Hayder F.; Altai, Alaa (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2024)
Diabetes mellitus represents a major health problem worldwide. DMis usually associated with hypovitaminosis D. Glycosylation is a non-enzymatic process associated with hyperglycemia. This work aims to explore the changes in glycosylation gap and VDR gene expression in type II DM patients with different vitamin D (vit. D) status in Mosul Province. This study recruit 300 subjects visiting Orkida's private laboratory for general screening tests. From May 2020 to August 2021, Only 80 of them fit the inclusion criteria of this work. They were divided into four groups of twenty each Serum fructosamine assay using the NBT-spectrophotometric methods12 and Vit D level estimation by using VIDAS® 25 OH Vitamin D Total - BIOMERIEUX using the Enzyme-Linked Fluorescent Assay (ELF) technique. Cells used for VDR qPCR analysis. The results of this work shows significant reduction in vitamin D levels between the three tested groups (p<0.05) in comparison to control. The glycosylation gap showed a significant elevated in all groups in comparison to the control-group (p<0.01). significant reduction was noticed in VDR expression in all groups in comparison to the control-group was noticed. VDR expression significantly reduced with elevation in glycosylation gap in both normoglycemic with low Vit D and type II diabetic with sufficient and insufficient vit D group.